PENGARUH PENAMBAHAN RAGI (Saccaromyces cerevesiae) DAN JUMLAH LUBANG KOTAK PADA FERMENTASI BUAH KAKAO (Theobroma cacao L) TERHADAP MUTU BIJI KAKAO KERING - wenceslaus hari kristanto; Tamrin .; Maria Erna (Jurnal Teknik Pertanian Lampung (Journal of Agricultural Engineering), 2017)
The high production of cocoa in Lampung has not been balanced with the good postharvest handling. The lack of post-harvest handling on the fermentation process causesthe low quality of cocoa Nib. The farmers did not do the fermentation process due to its time. This research aims to determine the effect of adding yeast (Saccaromyces cerevesiae) and the number of holes in the box of fermented cocoa (Theobroma cacao L.) on the quality of dried cocoa beans according to National Standardization. The materials used were cocoa fruit of mulia variety, Saccaromyces cerevesiae and fermentation box (26 x 25 x 23 cm). This research was designed with the RAK Factorial. The first factor was yeast additions (3 grams and 5 grams) and the second factor was the number of holes in the box (10, 20 and 30) which divided into three groups. The measured parameters were temperature, pH, water content, number of seeds per 100 grams, fat content, and cut test. The data was processed using analysis of variance (ANOVA) and LSD for further testing. The result of ANOVA showed that the diversity of the group, addition interaction of yeast and the number of holes in the box was not significant to affect all parameters. The factor of adding yeast affected the temperature, Cut test results and fat content while the number of holes factors affectd the cut test results and fat content. Based on these results, the amount of yeast addition was 5 grams and the best number of holes of fermentation box was 30 holes.Keywords: Cocoa, yeast addition, number of holes of fermentation box.